Effects of aeration, U.V. treated seawater and antibiotics on larval growth and spatfall in Pinctada fucata (Gould) - Dharmaraj, S; Shanmugasundaram, K (Indian Journal of Fisheries, 2011)
The larvae of the Indian pearl oyster Pinctada fucata were found to have been affected adversely by aeration during larval phase and consequently the growth, and spatfall were found to be poor. The values obtained in larval growth and spatfall were always less in U.V. treated seawater when compared to unsterilised seawater. This may be due to the destruction of nannoplankters by U.V. irradiation. Among the antibiotics tested, the performance of kanamycin was found to be better at 50 and 100 ppm in respect of growth and spatfall.